Analysis of the Role of Artificial Intelligence (AI) and Blockchain Technology in Improving the Effectiveness of Fraud Detection Audits: A Literature Review - Muhammad Alfiyan Putra Jarimanto; Duwi Rahayu (International Journal on Human-Computing Studies, 2026)
The development of digital technology has transformed auditing practices, particularly in improving fraud detection effectiveness. The complexity of financial transactions, large data volumes, and limitations of conventional audit methods have encouraged the adoption of technologies such as Artificial Intelligence (AI) and Blockchain. This study analyzes the role of AI and Blockchain in enhancing audit effectiveness in fraud detection using a systematic literature review (SLR) approach. The method follows PRISMA guidelines by reviewing nationally and internationally indexed articles published between 2022 and 2024. The findings indicate that AI supports large-scale data analysis, anomaly detection, and predictive as well as real-time fraud identification. Meanwhile, Blockchain enhances audit data integrity, transparency, and reliability through an immutable and decentralized recording system. The integration of these technologies promotes a more effective and sustainable auditing system, although challenges remain regarding human resource readiness, technological infrastructure, and ethical and legal considerations.